Blood flow kinetic energy is a novel marker for right ventricular global systolic function in patients with left ventricular assist device therapy - Akiyama, Koichi; Colombo, Paolo C.; Stöhr, Eric J.; Ji, Ruiping; Wu, Isaac Y.; Itatani, Keiichi; Miyazaki, Shohei; Nishino, Teruyasu; Nakamura, Naotoshi; Nakajima, Yasufumi; McDonnell, Barry J; Takeda, Koji; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives. Right ventricular (RV) failure remains a major concern in heart failure (HF) patients undergoing left ventricular assist device (LVAD) implantation. We aimed to measure the kinetic energy of blood in the RV outflow tract (KE-RVOT) – a new marker of RV global systolic function. We also aimed to assess the relationship of KE-RVOT to other echocardiographic parameters and assess the relationship of KE-RVOT to hemodynamic parameters of RV performance. Methods. Fifty-one subjects were prospectively enrolled into 4 groups (healthy controls, NYHA Class Ⅱ, NYHA Class Ⅳ, LVAD patients) as follows: 11 healthy controls, 32 HF patients (8 NYHA Class Ⅱ and 24 Class Ⅳ), and 8 patients with preexisting LVADs. The 24 Class Ⅳ HF patients included 21 pre-LVAD and 3 pre-transplant patients. Echocardiographic parameters (TAPSE, St’, Et’, IVA, MPI) and RV outflow color-Doppler images were recorded in all patients. Invasive hemodynamic parameters of RV function were collected in all Class Ⅳ HF patients. KE-RVOT was analyzed using a vector flow mapping software. Correlation between KE-RVOT and echocardiographic/hemodynamic parameters was assessed. Receiver operating characteristic curves for the ability of KE-RVOT to predict early phase RV failure were generated. Results. KE-RVOT (median±IQR) was higher in healthy controls (55.10 [39.70 to 76.43] mW/m) than in the Class Ⅱ HF group (22.23 [15.41 to 35.58] mW/m, p<0.005). KE-RVOT was further reduced in the Class Ⅳ HF group (9.02 [5.33 to 11.94] mW/m, p<0.05). KE-RVOT was lower in the LVAD group (25.03 [9.88 to 38.98] mW/m) than the healthy controls group (p<0.005). KE-RVOT had significant correlation with all echocardiographic parameters and no correlation with invasive hemodynamic parameters. RV failure occurred in 12 patients who underwent LVAD implantation in the ClassⅣ HF group. KE-RVOT cut-off value for prediction of RV failure was 9.15 mW/m (sensitivity: 0.67, specificity: 0.75, AUC: 0.66). Conclusions. KE-RVOT, a novel noninvasive measure of RV function, strongly correlates with well-established echocardiographic markers of RV performance. KE-RVOT is the energy generated by RV wall contraction. KE-RVOT may reflect global RV function. The utility of KE-RVOT in prediction of RV failure post LVAD implantation requires further study.